2020
DOI: 10.1029/2020jc016204
|View full text |Cite
|
Sign up to set email alerts
|

The Western Eurasian Basin Halocline in 2017: Insights From Autonomous NO Measurements and the Mercator Physical System

Abstract: We present the first sensor‐based profiles of the quasi‐conservative NO parameter obtained with an autonomous ice‐tethered buoy in the Arctic Ocean. Data documented the halocline in the Transpolar Drift and Nansen Basin in 2017. A NO minimum was found in the Nansen Basin on a σ‐horizon of 27.8 kg·m−3 corresponding to the lower halocline, while a lower NO minimum of 380 μM straddled the 27.4 σ‐horizon and marked the cold halocline in the Transpolar Drift. Back trajectories of water parcels encountered along the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Pfirman et al, 1994; Rudels et al, 2004; Steele et al, 1995). Recently, using the NO geochemical tracer, Bertosio et al (2020) showed that the base of the lower halocline which used to be associated with SA ~ 34.46 g/kg (34.3 psu) was now found on a saltier level of 34.9 g/kg in the Eurasian Basin. This denser level, corresponding to isopycnal 27.85 kg/m 3 , is in agreement with the deeper winter mixed layers reproduced by PSY4 in Nansen Basin: during the extreme winters 2012/13 and 2018/17, deep convection reached the 27.95 kg/m 3 isopycnal.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pfirman et al, 1994; Rudels et al, 2004; Steele et al, 1995). Recently, using the NO geochemical tracer, Bertosio et al (2020) showed that the base of the lower halocline which used to be associated with SA ~ 34.46 g/kg (34.3 psu) was now found on a saltier level of 34.9 g/kg in the Eurasian Basin. This denser level, corresponding to isopycnal 27.85 kg/m 3 , is in agreement with the deeper winter mixed layers reproduced by PSY4 in Nansen Basin: during the extreme winters 2012/13 and 2018/17, deep convection reached the 27.95 kg/m 3 isopycnal.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Exploratory 2‐D Lagrangian trajectories using PSY4 velocities suggested advective pathways from the continental slope to the center of the Nansen Basin in the 30–150 m layer (i.e. halocline waters), with time scales larger than 3 years (Bertosio et al, 2020). Full 3‐D Lagrangian tracking would extend this precursory work and improve our understanding of the fate of the convected water and its impact on the halocline water properties.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was supplemented with water chemistry measurements, primarily inorganic nutrients, alkalinity, barium and stable oxygen isotopes (Bauch et al., 1995; Guay & Falkner, 1997; Jones & Anderson, 1986). The increasingly widespread deployment of additional biogeochemical sensors (oxygen and a selection of optical probes) on profiling instruments offers higher resolution measurements and an opportunity to further explore processes involved with HL formation, and source fractionation of freshwater distribution (Athanase et al., 2019; Bertosio et al., 2020; Boles et al., 2020; Dmitrenko et al., 2019; Laney et al., 2014). A fraction of the organic compounds present in DOM fluoresce and this can be used as a proxy for dissolved organic carbon in the Arctic (Amon et al., 2003; Gonçalves‐Araujo et al., 2016; Guay et al., 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Pfirman et al, 1994;Rudels et al, 2004;Steele et al, 1995). Recently, using the NO geochemical tracer, Bertosio et al (2020) showed that the base of the lower halocline which used to be associated with SA~34.46 g/kg (34.3 psu) was now found on a saltier level of 34.9 g/kg in the Eurasian Basin. This denser level, corresponding to isopycnal 27.85 kg/m 3 , is in agreement with the deeper winter mixed layers reproduced by PSY4 in Nansen Basin: during the extreme winters 2012/13 and 2018/17, deep convection reached the 27.95 kg/m 3 isopycnal.…”
Section: Summary and Discussionmentioning
confidence: 99%